De la simulation à la simulation participative : apporter une vision intégrée de la rénovation urbaine aux aménageurs publics, à travers une démarche expérimentale - Anaïs Berry; Nicolas Becu; Onil Goubier; Nikolaos Papoulias; Nathalie Long; Didier Vye (Netcom)
part of national urban renewal programs, the political stakeholders of the city are engaged in many projects seeking to achieve different purposes: reduce energy consumption, improve living condition, foster ecomobility, promote social mixing. The public and local stakeholders involved (policy services of the city, urban planning and environment services of municipalities and inter-municipal associations, providers of social housing) are asked to provide their expertise and advice. However, these stakeholders may lack time, resources and methods to work together. That’s why in the context of a multidisciplinary project on energy efficiency scaling from occupant to building and urban levels, the participatory simulation platform “Geranium” has been developed to propose to decision makers an integrated approach of a renewal program of a priority neighborhood. The participatory simulation development is based on two phases: development of an integrated simulation model for energy consumption, then its adaptation into a participatory simulation. The numeric model allows the simulation of energy consumption of households for a set of buildings (« la Cité des Géraniums » in the district of Saint-Éloi in La Rochelle), for which an urban renewal project has been initiated in 2009. In the Geranium model, the participants can change three main classes of parameters during a simulation session: building structural parameters (number, surface, energy performance), psycho-social parameters of the households (household structure, income, occupant status, environmental awareness) and micro-climate parameters (temperature, humidity). Data and parameters of the Geranium model are the outcome of household surveys as well as scientific and grey literature sources. The transposition of this model into a participatory simulation is designed as a numeric modeling whose participatory use is envisaged through the integration of game mechanics and a screenwriting to be experiment with the participatory simulation. The objective of the participatory simulation is to lead the participants to reflect on an urban renewal project whilst reconciling the challenges of energy consumption, social mixing, housing and all this while taking into account climate change.